Recent developments in Salvia miltiorrhiza polysaccharides: Isolation, purification, structural characteristics and biological activities - Lei Luo; Juan Xue; Juan Xue; Zheng Shao; Zhang Zhou; Wenqian Tang; Jinxin Liu; Hongfei Hu; Fan Yang (Frontiers Media S.A., 2023)
In recent years, natural polysaccharides have attracted more and more attention and research because of their value in the medicine, beauty and food fields. Salvia miltiorrhiza is a traditional Chinese herb that has been used for thousands of years and has antidiabetic, antifibrotic, neuroprotective, antioxidation, anti-inflammatory and other effects. It mainly includes rosmarinic acid, tanshinone I, tanshinone IIA, tanshinone IIB, procatechualdehyde, polysaccharide and salvianolic acids. Salvia miltiorrhiza polysaccharide is a polysaccharide extracted and isolated from Salvia miltiorrhiza and has diverse biological functions, including antioxidation, anti-tumor, hepatoprotective, anti-inflammatory, immune regulatory and cardioprotective effect. In this review, the extraction, purification, structural characterization and biological activity of SMPs are summarized and new perspectives for the future work of SMPs were also proposed, we hope our research can provide a reference for further research on SMPs.